Development and psychometric properties of a Calcium Intake Questionnaire based on the social cognitive theory (CIQ-SCT) for Iranian women - Mahin Nematollahi; Ahmadali Eslami (Tabriz University of Medical Sciences, 2018)
Background: Osteoporosis is common among women which may be mostly due to the low intake of calcium. This article reports the development, cultural adaptation and psychometric properties of a Calcium Intake Questionnaire based on the social cognitive theory (CIQ-SCT)among Iranian women.Methods: In 2016, this cross-sectional study was carried out among 400 younger than 50 years old women in Isfahan, Iran. After literature review, a preliminary 35-item questionnaire was developed. Then, forward-backward translation and cultural adaptation of the tool was conducted. Content Validity Index confirmed by an expert panel and Face Validity was evaluated in a pilot study. Exploratory and confirmatory factor analyses (EFA &CFA) were conducted on the calibration and validation sample, respectively. Reliability was also assessed using internal consistency test.Results: After determining content and face validity, 20 items with 5 factors (self-efficacy,outcome expectations, social support and self-regulation) were obtained. Cronbach alpha for the instrument was found to be 0.901. In EFA, we identified a 4-factor model with a total variance of 72.3%. The results related to CFA (CMIN/DF=1.850, CFI =0.946, TLI=0.938, RMSEA=0.069[90% CI: 0.057-0.081]) indicated that the model was fit to the social cognitive theory. Self regulation was detected as the best predictor for calcium intake.Conclusion: The CIQ-SCT showed acceptable levels of reliability and validity in explaining the calcium intake based on the constructs of social cognitive theory. Further psychometric testing is recommended in different population to approve the external validity of the instrument.